Evaluation and Treatment of Obesity and Its Comorbidities: 2022 Update of Clinical Practice Guidelines for Obesity by the Korean Society for the Study of Obesity - Kyoung-Kon Kim; Ji-Hee Haam; Bom Taeck Kim; Eun Mi Kim; Jung Hwan Park; Sang Youl Rhee; Eonju Jeon; Eungu Kang; Ga Eun Nam; Hye Yeon Koo; Jeong-Hyun Lim; Jo-Eun Jeong; et al. (Journal of Obesity & Metabolic Syndrome, 2023)
The goal of the 8th edition of the Clinical Practice Guidelines for Obesity is to help primary care physician provide safe, effective care to patients with obesity by offering evidence-based recommendations to improve the quality of treatment. The Committee for Clinical Practice Guidelines comprised individuals with multidisciplinary expertise in obesity management. A steering board of seven experts oversaw the entire project. Recommendations were developed as the answers to key questions formulated in patient/problem, intervention, comparison, outcomes (PICO) format. Guidelines underwent multi-level review and cross-checking and received endorsement from relevant scientific societies. This edition of the guidelines includes criteria for diagnosing obesity, abdominal obesity, and metabolic syndrome; evaluation of obesity and its complications; weight loss goals; and treatment options such as diet, exercise, behavioral therapy, pharmacotherapy, and bariatric and metabolic surgery for Korean people with obesity. Compared to the previous edition of the guidelines, the current edition includes five new topics to keep up with the constantly evolving field of obesity: diagnosis of obesity, obesity in women, obesity in patients with mental illness, weight maintenance after weight loss, and the use of information and communication technology-based interventions for obesity treatment. This edition of the guidelines features has improved organization, more clearly linking key questions in PICO format to recommendations and key references. We are confident that these new Clinical Practice Guidelines for Obesity will be a valuable resource for all healthcare professionals as they describe the most current and evidence-based treatment options for obesity in a well-organized format.